Influence of one-dimensional material flow on mechanical properties and fiber orientation distribution of thin-ply carbon fiber reinforced thermoplastics sheet molding compounds - Zhao, Zihao; Wan, Yi; Xu, Xiaodong; Takahashi, Jun (Elsevier, 2024)
The molding flow of carbon fiber reinforced thermoplastic sheet molding compounds (CFRTP-SMC) is complex and requires a comprehensive understanding of underlying processes. This study investigates the material behavior during compression molding processes, focusing on the influence of the ratio of initial material charge area over mold area (charge ratio) on mechanical properties. The results highlight the CFRTP-SMC material's excellent flowability and moldability and confirm that the mechanical properties and internal morphology change with charge ratios. In addition, a correlation between mechanical properties and internal morphology is established through quantitative analysis of fiber orientation distributions using X-ray computed tomography. This comprehensive investigation not only sheds light on the molding ‘behavior of CFRTP-SMCs, but also underscores the importance of material charge ratios in influencing the mechanical properties. This study also provides a case study for validating numerical process models.
Keywords: Molding compounds; Directional orientation; CT analysis; Compression molding; 40 Engineering; 4016 Materials Engineering